EFFECT OF ULTRASOUND TREATMENT COMBINED WITH SODIUM HYDROGEN SULFITE ON THE QUALITY OF POSTHARVEST LONGAN FRUIT - Trung Truc, Nguyen; Khanh Thi, Huynh; Thi Cam Nhung, Duong (HNUE Journal of Science: Journal of Natural Sciences, 2025)
Longan is one of the fruits with a high economic value in Vietnam and is grown in both Northern and Southern provinces. However, the quality of longan fruits deteriorates quickly after harvest. The study aimed to combine ultrasound (US) treatment with a sodium hydrogen sulfite (SHS) solution as the wave transmission medium to reduce color changes and maintain the quality of longan fruit during storage at 25℃. Longan fruit was treated with US at a frequency of 192 kHz combined with SHS solutions at concentrations of 0.25% and 0.5% (w/v) for 1.5, 2.5, and 5.0 minutes. The results showed that the 0.5% SHS + US 1.5 min treatment effectively delayed color change of longan peel and reduced weight loss of the fruit, but did not affect the edible quality, including total titratable acidity and soluble solid content (oBrix), while maintaining vitamin C, total phenolic content, and antioxidant activity of longan fruit, compared to the control during 8 days of storage at 25℃. These results suggest that ultrasound treatment combined with sodium hydrogen sulfite can be potentially used for the preservation of longan fruit.